(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In short we can characterize Psycho-neurobics as-’Procedure of taking astronomical vitality present in the universe by the intensity of brain (the source is GOD) and after that exchanging it to brain and neurosystem’ We can mend any sort of illness by psycho-neurobics and actuate our seven vitality focuses present in the body. The word psycho remains for ’mind’ as we take the vast vitality through the intensity of brain. There are three sorts of neurobics LIGHT NEUROBICS, SOUND NEUROBICS AND EASY NEUROBICS in Psycho-neurobics we incorporate all the three neurobics.